Improving infiltration on irrigated Mediterranean soils with polyadrilamide - Santos, Francisco Lúcio (2000)
Abstract The effects of continuous (1·0 mg/l) and concentrated (10 mg/l) irrigation water-added polyacrylamide (PAM) on infiltration of a highly erodible Mediterranean soil were studied using recirculating furrow infiltrometers. Polyacrylamide avoided the seal formation observed in the wetted surface of the control furrow and helped to maintain higher infiltration rates for both PAM treatments. Mean final cumulative infiltration for the continuous and concentrated PAM experiments increased by 20 and 14%, respectively, as the result of reduced seal formation and surface sealing. Steady-state furrow infiltration rates, evaluated with disc infiltrometers 15 h after irrigation and under soil water tensions of 40 and 100 mm, confirmed the infiltration benefit of PAM treatments. Unsaturated hydraulic conductivity calculated under the same tensions revealed that the PAM-treated furrows were about 95% more permeable than the control. Polyacrylamide application also increased average saturated conductivity by 168% because of more unblocked pores in the treated furrows. The ability of PAM to influence surface soil conditions and improve infiltration can greatly enhance management of irrigated Mediterranean soils by allowing longer irrigation and higher inflow rates. Application of 10 mg/l in the inflow only during the advance phase of the irrigation can reduce labour, and ensures that loss of PAM from furrow tail water is minimized and that quantities applied during the season are reduced.